Current approaches to therapy for complications of bone metastases from breast cancer - L. G. Zhukova (Опухоли женской репродуктивной системы)
In breast cancer, bone metastases are detectable in more than 60 % of patients. Bone metastasis-related complications (BMRCs), such as chronic pain, immobilization, and pelvic dysfunctions due to spinal cord compression, considerably worsen quality of life in patients. Intra- venous formulations of bisphosphonates (zoledronic acid, pamidronate, ibondronate, and clodronate) could reduce the risk of BMRCs by 16-40 % and increase time to the first skeletal complication up to 12–13 months. However, despite the explicit clinical efficacy of bisphospho- nates, the latter can seemingly prevent only some BMRCs. Denosumab, a fully human monoclonal antibody to RANKL, suppresses the forma- tion and functional activity of osteoclasts, thus inhibiting bone resorption.The results of a registration study have indicated that denosumab is not only as effective as zoledronic acid, but also can reduce the risk of BMRCs and significantly delay time to the first and further skeletal complications, including the need for radiotherapy, the development of hypercalcemia and pathological fractures. Denosumab is an effective, well-tolerated drug that can increase a chance of preventing BMRCs in breast cancer.